Bioengineering of High Cell Density Tissues with Hierarchical Vascular Networks for Ex Vivo Whole Organs. Issue 9 (1st January 2023) - Wu, Peizheng; Asada, Hiroki; Hakamada, Masataka; Mabuchi, Mamoru
Abstract: The development of tissue‐like structures such as cell sheets, spheroids, and organoids has contributed to progress in regenerative medicine. Simultaneous achievement of scale up and high cell density of these tissues is challenging because sufficient oxygen cannot be supplied to the inside of large, high cell density tissues. Here, in vitro fabrication of vessels to supply oxygen to the inside of millimeter‐sized scaffold‐free tissues whose cell density is ≈200 million cells mL −1, corresponding to those of native tissues, is shown. Hierarchical vascular networks by anastomosis of capillaries and a large vessel are essential for oxygen supply, whereas a large vessel or capillary networks alone make negligible contributions to the supply. The hierarchical vascular networks are formed by a top‐down approach, which offers a new option for ex vivo whole organs without decellularization and 3D‐bioprinting. Abstract : A novel method is shown to fabricate an in vitro model of millimeter‐sized scaffold‐free tissues whose cell density is ≈200 million cells mL −1, corresponding to those of native tissues. The supply of oxygen and nutrition is extremely significant for such tissues. Therefore, a hierarchical vascular network containing capillaries and an artificial channel for perfusion are formed.